Efektivitas Tapping Box Terhadap Pendapatan Asli Daerah Kota Ambon - James Pelupessy (Jurnal Administrasi Terapan, 2024)
This research analyzes the benefits of implementing policies and the accuracy of Tapping Box targets in monitoring regional restaurant taxes in Ambon CityThe right policy and the right target are criteria that must be met for a policy to be considered successful in a qualitative data analysis approach. The implementation of the Tapping Box policy and setting targets as a means of monitoring regional taxes can be categorized as effective. Keywords: Tapping Box, Restaurant Tax, effective